β-Catenin Protein and Its Association with Helicobacter Pylori as A Possible Marker for Gastric Cancer - K Al-Bayaty, Mustafa; A Abass, Salma; F Al-Marjani, Mohammed (Al-Nahrain Journal of Science, 2019)
Gastric cancer is still the main health threat being the third leading cause of deaths from cancers in the world, the major risk behind this disease is that it remains asymptomatic in the early stages and in (97 %) cases it metastasizes to other organs. Gastric cancer is a multifactorial disease with Helicobacter pylori (H. pylori) being the major risk factor, however, patients with gastritis, especially atrophic gastritis and gastric ulcer have been shown to be at an increased risk for developing gastric cancer. In this research, serum β-catenin, carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA 19-9) were measured in patients diagnosed with gastric cancer, gastric ulcer and gastritis and also in healthy volunteers. Infection with Helicobacter pylori (H. pylori) was diagnosed by histological test, rapid urease test (RUT) and by serological tests which included IgG and IgA antibodies. The results showed that there was a large significant increase in the levels of serum β-catenin in patients with gastric cancer compared to the control group as well as to the gastritis and gastric ulcer patients. A significant increase was also seen in gastric ulcer and gastritis patients when compared to the control group. In addition, a significant increase was seen in β-catenin serum levels in patients with gastric cancer and gastric ulcer infected with H. pylori compared to the uninfected gastric cancer and gastric ulcer patients. A non-significant change was observed in the levels of CEA and CA 19-9 in all the patients compared to the control group. The results of this study suggest that β-catenin can serve as a potential biomarker for the diagnosis of gastric cancer and that H. pylori has a significant effect on the levels of this protein.